TRANSLATION OF NEGATIONS IN PRAMOEDYA ANANTA TOER’S NOVEL BUMI MANUSIA AND IT’S PEDAGOGICAL IMPLICATION - Ulin Ni’mah Rodliya Ulfah (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2016)
This study is aimed at (1) identifying the kinds of Indonesian negation found in Bumi Manusia which are translated into English; (2) analyzing the various strategies used by the translator to translate negations in the novel Bumi Manusia into English; and (3) evaluating the appropriateness of the translation of negation from Indonesia into English and describing its pedagogical implications. This study uses a descriptive-qualitative research design. The data of the research are negations found in three chapters (chapter 1, 3, and 5) of the novel Bumi Manusia and in their translation This Earth of Mankind. The result shows that of the 69 pages of the novel BumiManusia, 329 negation in simple sentences are identified. They are divided into three types: standard negation, negation and adverb, and negation and quantity. In translating the Indonesian negation in the novel BumiManusia, this study finds that strategies which have been applied are adopted from the seven strategies proposed by Newmark. Of 329 negation, 205 or 62.3% dominantly applied the strategy of reproducing or adopting the same image of negation in the TL text. In relation to the evaluation of the translation appropriateness, the result shows that from 329 negation 308 or 93.6% are translated appropriately. Meanwhile, 19 translation of negation or 5.8% are categorized as less appropriate translation, and 1 translation of negation or 0.3% is rendered inappropriately